Uma investigação em textos dissertativo-argumentativos de alunos do 1 ano do ensino médio regular da rede pública de Bacabal - MA: o ensino da argumentação - SOUZA, Rannyelle Natallya Pereira de (2021)
Argumentation, according to Fiorin (2018), is a fact of language, a natural ability, in other words, all human beings have argumentative potential. With this idea as a basis, this research aims to identify and analyze the strategies and argumentative operators frequent in the production of dissertation-argumentative texts by first-year high school students in the state school system of Bacabal, observing how this construction occurs. according to specific resource choices over others. It also aims to present a discussion about the teaching of argumentation at school. Some discussions by scholars on the subject, such as those produced by Perelman and Olbrechts-Tyteca (2005) and their considerations on argumentation in the new rhetoric; Plantin (2008) and the perspective of linking argumentation to logic, rhetoric and dialectics, Amossy (2018) and the foundation of argumentative schemes in discourse; Koch (2018) with the specifications of the argumentative operators, were some of the theories presented to guide the research and, consequently, for the analysis of the texts. The work considered in its analysis texts by high school students on a controversial subject, the well- known “Brazilian way”, the theme of a project carried out by the Public Ministry in partnership with state schools, analyzing their point of view, as well as their organizations argumentative, based mainly on the argumentative techniques of Perelman and Olbrechts- Tyteca and on the argumentative schemes of Amossy. This work, in addition to analyzing the construction of argumentation through the argumentative strategies used, aims to provide, through these productions and their characteristics, a reflection on argumentation in the school environment, especially in High School, showing as a result that 1st year students of high school students are, yes, able to argue, as we see through the identification and analysis of argumentative strategies.